Influence of lipopolysaccharide-induced immune challenge and diet complexity on growth performance and acute-phase protein production in segregated early-weaned pigs - Owen, K.Q.; Chengappa, M. M.; Blecha, Frank; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
When eating the same amount of feed, pair-fed pigs were more efficient at using nutrients for growth than pigs injected with lipopolysaccharide (LPS). Approximately 2/3 of the decreased growth of LPS-challenged pigs was due to decreased ADFI and 1/3 was due to decreased feed efficiency (F/G). Determining the optimum diet complexity for a nursery feeding program will depend on the desired balance between growth performance. and feed cost per lb of gain but appears to be independent of immune response to inflammatory challenge. On a practical basis, this suggests that nursery diet complexity should not be influenced by health status.
Keywords: Swine; Diet complexity; Lipopolysaccharide; Growth